The benefits and burdens of care: A gendered analysis of American elementary school teachers navigating uncertainty at the onset of the COVID-19 pandemic - Cohen, Elisheva; Willemsen, Laura Wangsness (Frontiers in Education, 2022)
This paper brings together anthropology of uncertainty and gender and education to examine the gendered daily experiences of elementary level teachers in the United States at the onset of the COVID-19 emergency. We found that teachers responded to ongoing uncertainty through various forms of care both at work and home: care for students and their families, their colleagues, their school community, their own families, and when possible, themselves. We argue that this care work served as a key mechanism that teachers used to navigate the uncertainty posed by the pandemic while simultaneously serving as a weight that exacerbated their stress, anxiety, and workload, and ultimately limited their capacity to care for themselves. Additionally, we argue that the care-laden responses of elementary school teachers to this crisis both reflect and reify the particularly gendered ways that women are tasked with the necessary work of nurturing in schools as well as in families. This work makes a theoretical contribution to the literature on education in emergencies by framing the concept of emergency through the lenses of uncertainty and gender. We show how providing education in emergency settings can be a productive process functioning along relational and temporal axes. Furthermore, we shed light on the day-to-day work of teachers in a global health emergency and provide a framework for understanding the immense and often gendered care work they do. Finally, by situating this article in the United States, we seek to highlight the presence of emergencies across the Global North, thereby making a case for extending the concept of emergency within the field of education in emergencies beyond the Global South. By examining early pandemic patterns of intensive care work conducted by teachers, this paper helps to explain the global crisis of teacher burnout and attrition 2 years after the pandemic began and offers insight for those seeking to prevent teacher burnout in the next emergency.